Proceedings of the Mathematics, Informatics, Science, and Education International Conference (MISEIC 2018) 2018
DOI: 10.2991/miseic-18.2018.1
|View full text |Cite
|
Sign up to set email alerts
|

Designing Teaching Material Oriented Towards Inquiry-Based Learning in Biology

Abstract: The inquiry-based learning model is the model suggested for learning in the 21 st century. This learning process will succeed if supported by teaching material that prepares students for real-life situations. This research aimed to design and develop valid teaching material that is oriented towards inquiry-based learning. The research method used was a 4-D model. The process started with the defining stage and the design and development of teaching material (included validation and small group trials). A pilot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
2
0
5
Order By: Relevance
“…The results of experts and FGD's validation showed that the teaching materials were valid and may be tested in class learning process. Result of validation was presented in International Conference (Damopolii, Nunaki, Nusantari, & Kandowangko, 2018. ) In this stage, the developed teaching materials will be tested for their effectiveness in the metacognitive skill of students of Public Senior High School 01 Manokwari, Indonesia.…”
Section: Methodsmentioning
confidence: 99%
“…The results of experts and FGD's validation showed that the teaching materials were valid and may be tested in class learning process. Result of validation was presented in International Conference (Damopolii, Nunaki, Nusantari, & Kandowangko, 2018. ) In this stage, the developed teaching materials will be tested for their effectiveness in the metacognitive skill of students of Public Senior High School 01 Manokwari, Indonesia.…”
Section: Methodsmentioning
confidence: 99%
“…The Inquiry-based student book that the researchers use in this research was a development result product (Damopolii, Nunaki, et al, 2018). Therefore, this student book has met the criteria for use in learning.…”
Section: Methodsmentioning
confidence: 99%
“…Lebih lanjut Imam et al (2017) model inkuiri terbimbing dapat meningkatkan hasil belajar siswa, apabila guru menerapkan proses pembelajaran yang menuntut keterlibatan siswa secara aktif di dalamnya sehingga kemampuan untuk menganalisis dan mengevaluasi informasi akan berkembang dengan masalah yang dihadapi oleh siswa. Beberapa penelitian menyimpulkan bahwa pembelajaran inkuiri mempunyai pengaruh terhadap, keterampilan proses sains, sikap ilmiah, keterampilan berpikir kritis dan hasil belajar (Damopolii et al, 2015;Damopolii et al, 2018;Hadi et al, 2018;Mayasari et al, 2018;Nisa et al, 2018).…”
Section: Pendahuluanunclassified